2020
DOI: 10.1007/s40194-020-00927-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the ultrasonic joining process parameters effect on the mechanical properties of metal-composite hybrid joints

Abstract: The ultrasonic joining process was recently introduced as an alternative concept to join through-the-thickness reinforced metal-composite hybrid structures. In this work, the investigation of joining process parameters effect on the joint mechanical performance of Ti-6Al-4V-glass-fiber-reinforced polyetherimide overlap joints was carried out by Box-Behnken design of experiments. The individual and combined effects of joining energy, sonotrode oscillation amplitude, and joining pressure on the ultimate lap shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Mostly, pins have a cylindrical or rectangular cross section [18] depending on the manufacturing process or desired mechanical properties. Pin structures for joining dissimilar materials are produced by various manufacturing processes, which can be primarily categorized as molding [19], additive [20] and formative [21]. Pin joints mostly are known for metalmetal joints [22] as well as metal-composite (thermoset [23] and thermoplastic [21] matrix systems) joints.…”
Section: Pin Joiningmentioning
confidence: 99%
“…Mostly, pins have a cylindrical or rectangular cross section [18] depending on the manufacturing process or desired mechanical properties. Pin structures for joining dissimilar materials are produced by various manufacturing processes, which can be primarily categorized as molding [19], additive [20] and formative [21]. Pin joints mostly are known for metalmetal joints [22] as well as metal-composite (thermoset [23] and thermoplastic [21] matrix systems) joints.…”
Section: Pin Joiningmentioning
confidence: 99%
“…Transversal to the fibre direction, bending and shifting can occur. The superposition of bending and shifting is often termed reorientation [ 18 , 25 , 26 ], rearrangement [ 7 ], or displacement [ 9 ]. In the following, the term reorientation is used.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of suitable low-heat joining methods for hybrid joints such as for example ultrasonic welding (USW) [6][7][8], friction stir spot welding (FSSW) [9], or adhesive bonding [10] is not the only engineering challenge. Although the joining technology of FSSW can produce a favorable mechanical interlocking between aluminum and loadbearing fibers, damage to the CFRP laminate due to fiber fracture and delaminations caused by the process was observed [11].…”
Section: Introductionmentioning
confidence: 99%
“…This method is already being used in research to characterize, analyze, and evaluate for example polymer and metal matrix composite materials [16][17][18] or material composition due to advanced manufacturing or joining processes [19][20][21][22]. X-ray tomography and 3D reconstruction of µCT-measurements has been performed on bolted FRP joints to quantify failure mechanics [23] and on ultrasonically welded hybrid joints to gain structural information on a macroscopic level [8]. Previous research on the ultrasonic joining process for fiberreinforced thermoplastics has shown that selected and controlled process parameters can have a significant influence on the overall process, at particular temperatures occurring in the joining zone and the development of the joint [24].…”
Section: Introductionmentioning
confidence: 99%